1998
DOI: 10.1073/pnas.95.16.9687
|View full text |Cite
|
Sign up to set email alerts
|

MsPG3 , a Medicago sativa polygalacturonase gene expressed during the alfalfa– Rhizobium meliloti interaction

Abstract: Polygalacturonase (PG) is one of the most important enzymes associated with plant cell wall degradation. It has been proposed to participate in the early steps of the Rhizobium-legume interaction. We have identified two classes of cDNA fragments corresponding to two classes of PG genes in the Medicago genome. One of this class, represented by E 2 in M. truncatula and Pl 1 in M. sativa, seems to be related to previously characterized plant PG genes expressed in pollen. We have isolated the genomic clone contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 30 publications
0
37
0
2
Order By: Relevance
“…Cell wall degradation is essential to processes such as root hair initiation, fruit ripening, pollen tube elongation and leaf abscission. In addition, symbiosis-specific expression of polygalacturonases and pectin methylesterases was observed during the early steps of the S. meliloti-Medicago interaction (Munoz et al, 1998;Rodriguez-Llorente et al, 2004). So, instead of degrading plant cell walls themselves, rhizobia might induce the expression of degradative host enzymes to the same effect, and a deficiency such as that caused by mutation of hrpW could be masked.…”
Section: Discussionmentioning
confidence: 99%
“…Cell wall degradation is essential to processes such as root hair initiation, fruit ripening, pollen tube elongation and leaf abscission. In addition, symbiosis-specific expression of polygalacturonases and pectin methylesterases was observed during the early steps of the S. meliloti-Medicago interaction (Munoz et al, 1998;Rodriguez-Llorente et al, 2004). So, instead of degrading plant cell walls themselves, rhizobia might induce the expression of degradative host enzymes to the same effect, and a deficiency such as that caused by mutation of hrpW could be masked.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that some cell wall-degrading enzymes could be involved in the early steps of Rhizobiumlegume interactions (Muñoz et al 1998;Rodriguez-Llorente et al 2004). It is probable that these enzymes facilitate penetration by hydrolysing the cell wall of bacteria in plant cells.…”
Section: Ghs In Symbiosismentioning
confidence: 99%
“…It was recently shown that an alfalfa polygalacturonase gene (MsPG3) was induced specifically in roots in response to S. meliloti (111). The gene was induced as early as 1 day after spot inoculation, and high levels of expression of this gene were seen in the nodule meristem, infection zone, and interzone II-III of nodules.…”
Section: Degradation Of Cell Wall Associated With Infection Thread Inmentioning
confidence: 99%